Cerebral Oxygenation during Apnea in Preterm Infants: Effects of Accompanying Peripheral Oxygen Desaturation - Seo Hee Choi; Juyoung Lee; Soo Kyung Nam; Yong Hoon Jun (Korean Society of Neonatology, 2021)
Purpose Premature infants have immature respiratory control and cerebral autoregulation. We aimed to investigate changes in cerebral oxygenation during apnea with and without peripheral oxygen desaturation in premature infants. Methods This prospective observational study was conducted at Inha University Hospital. Near-infrared spectroscopy (NIRS)-monitored regional cerebral oxygen saturation (rScO2) and pulse oximeter-monitored peripheral oxygen saturation (SpO2) were assessed during the first week of life in 16 stable, spontaneously breathing preterm infants. Apneic episodes that lasted for ≥20 seconds or were accompanied by desaturation or bradycardia were included for analysis. The average rScO2 value during the 5-minute prior to apnea (baseline), the lowest rScO2 value following apnea (nadir), the time to recover to baseline (recovery time), the area under the curve (AUC), and the overshoot above the baseline after recovery were analyzed. Results The median gestational age and birth weight of the infants were 29.2 weeks (interquartile range [IQR], 28.5 to 30.5) and 1,130 g (IQR, 985 to 1,245), respectively. A total of 73 apneic episodes were recorded at a median postnatal age of 2 days (IQR, 1 to 4). The rScO2 decreased significantly following apneic episodes regardless accompanied desaturation. There were no differences in baseline, nadir, or overshoot rScO2 between the two groups. However, the rScO2 AUC for apnea with desaturation was significantly higher than that for apnea without desaturation. Conclusion Cerebral oxygenation can significantly decrease during apnea, especially when accompanied by reduced SpO2. These results add the evidence for the clinical utility of NIRS in monitoring premature infants.